Identifikasi Sumber Air Sebagai Upaya Konservasi di Kecamatan Singosari Kabupaten Malang - Finahari, Nurida; Soebiyakto, Gatot (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Singosari District, Malang Regency, which is located at the foot of the mountain, is an area that has many water sources. This activity is carried out to identify problems and potentials that can endanger this natural resource. Activities are carried out by direct visits to 3 source locations. The results of the visit showed that around the location there were still many trees to support water sources. Utilization by the community can cause potential environmental damage in the form of non-organic waste. Community service activities can be carried out in the form of educating the community.